Issues on the identity of a professional counselor - Mochamad Nursalim (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
Until now there is still some doubt in formulating a professional identity of counselors in Indonesia, There are those who want education for counselors candidate in Indonesia leads to specialization of school counseling, career counseling, or personal counseling; and is focused on development, prevention rather than medical/clinical models. Aggrement that has not been set up yet among counselor education providers has made the identity of professional counselors increasingly not clear. This paper seeks to review current issues related to the identity of professional counselors. Based on conceptual studies, it can be asserted that the identity of professional counselors is prominent and unique is the key to the profession in order to develop and not be marginalized, and parallel to other mental health professions. the adoption of SK Kemenristekdikti number 257/M/KPT/2017 about the name of the study program at the college, which contains the name of counselor profession education (Counselor profession Education) with a degree Kons. very influential on the development of the identity of professional counselors in Indonesia.